PENGARUH CO BRANDING DAN PROMOSI PENJUALANTERHADAP KEPUTUSAN MENGGUNAKANOPERATOR TELEPON SELULER CDMA - Sri Yusmalinar, - (2007)
Sri Yusmalinar, TheInfluence ofCo branding and Sales Promotion on CDMA cellularphone operator using Decision, (Surveyon CDMA cellularphone operator user at BandungElectronic Center, Purnawarman St Bandung), underguidance Dr Agus Rahayu, Msi and Dr. Vanessa Gaffar, SE.Ak.MBA. Thedevelopmentofcommunication technology and information, as one ofthe fields that was very starategic in the age 21 emerged to technology that was dominant in the life ofhumankindand held the importantrole in all the aspect ofthe life,from social, economics, politics, culture, to theprivate private matter. One ofthe implements and sophisticated information ofcommunication technology that was developing was at this timeand often used by the community, that is the cellular phone. Thedeveloping andpopular cellular phone at this time that is having GSM ( Global System Mobile Communication) as a base and CDMA (Code Division Multiple Access). This research had a purpose to know ; (I) Theresponse co branding the CDMA cellularphone operator according to the user ofthe CDMAcellularphone operator in BEC, (2) Thepicture ofsales promotion ofCDMA cellularphone operator to the user ofthe CDMA cellular phone operator, (3) The decision used the CDMA cellular phone operator who was done by the user ofthe CDMA cellular phone operator in BEC, (4) It was a big that the influence co branding and sales promotion towards the decision to used the CDMA cellularphone operator in BEC TheResearch is based on descripetive and verificative type and it is conductedby descriptive survey and explanatorysurvey. Thedata are collected by questionnaire, interview, andfield observation. Theprimary data is composedfrom a numberofsamples of200 respondents. Method ofanalysis is path analysis. From the results ofthe research shows the response co branding the CDMA cellularphone operator according to the users response revolved abaout the category was enough: that is enough believed towards the make handset, was enough the experiencewith theproduct, quiteexact in choosing thepartner, thepicture of sales promotion ofCDMA cellular phone operator according to the user revolved about the category was enough: thai is quite exact in the aim, the message and sales promotion media that was carried out so as the CDMA company ofthe cellularphone operator must continue to increase their marketing strategy through co branding and sales promotion. The influence ofCo branding and sales promotion contributes 56,95% on CDMA cellularphone operator using decision.